Design of triple band antenna for energy harvesting application - Siti Nur Illia, Abdullah; Mohd Muzafar, Ismail; Jeefferie, Abd Razak; Zahriladha, Zakaria; Siti Rosmaniza, Ab Rashid; Nor Hadzfizah, Mohd Radi (Institute of Advanced Engineering and Science, 2022)
Energy harvesting is a fast-expanding topic in many scientific and engineering-related disciplines due to the extreme necessity to discover answers to the world's power challenges. This paper focuses on the design of a novel antenna that will operate at frequencies of 2.45 GHz, 4.5 GHz, and 5.725 GHz. The study shows the improvement of the current triband antenna for energy harvesting applications by varying the antenna parameters. The return loss, the voltage standing wave ratio (VSWR) and the radiation pattern for the antenna at all frequencies 2.45 GHz, 4.5 GHz, and 5.725 GHz have been compared in the results. The scope of this project development comprises the antenna design utilizing simulation software, computer simulation technology (CST) 2019 and vector network analyzer (VNA) test instrument for physical testing. During the design process, fundamental antenna characteristics were estimated and validated to determine optimal performance of an antenna for this project.